Internet-Delivered Cognitive Behavior Therapy as a Prequel to Face-To-Face Therapy for Depression and Anxiety: A Naturalistic Observation - Duffy, Daniel; Enrique, Angel; Connell, Sarah; Connolly, Conor; Richards, Derek (Frontiers in Psychiatry, 2020)
a stepped care model treating individuals with depression and anxiety disorders. Internet-delivered cognitive behavioural therapy (iCBT) is routinely offered to individuals with mild to moderate symptoms, but its applicability to individuals with severe clinical symptoms and requiring a high-intensity intervention is relatively unknown. The current study sought to investigate the potential impacts of using iCBT as a prequel for patients requiring high-intensity treatment (HIT; face-to-face) for depression and anxiety in IAPT. Methods: The study utilised an open study design. 124 participants who were on a waiting list for high-intensity, face-to-face psychological treatment, were offered iCBT. Psychometric data on symptoms of depression, anxiety and functioning were collected from participants before starting and on finishing iCBT and at the point of service exit. Therapeutic alliance data was collected from patients and clinicians during treatment. Patient pathway data, such as number of treatment sessions and time in treatment, was also collected and incorporated into the analysis. Results: Significant reductions across primary outcome measures of depression and anxiety, as well as improved functioning, were observed from baseline to iCBT treatment exit, and from iCBT exit to service exit. Analysis of the therapeutic alliance data for patients and clinicians illustrated differences in outcome for those who dropped out and those who completed treatment. Discussion: This study illustrates the potential for using iCBT as a prequel to high intensity therapy for depre¬ssion and anxiety disorders and is the first of its kind to do so within IAPT stepped-care. The results show that iCBT is a valuable option reducing waiting times and enhancing clinical efficiency. The study contributes to the well-established evidence on online psychological treatments worldwide, but further clinical and service development research is necessary to scale these treatments appropriately.